The Wiley-Blackwell companion to cultural geography - Johnson, Nuala Christina, 1962- (Chichester, West Sussex : Wiley-Blackwell, 2013)
'A significantly revised new edition of this authoritative reference volume which traces the historical evolution of cultural geography through to the very latest research'--
Includes index.
Keywords: Human geography; SOCIAL SCIENCE / Human Geography